MAC Project—Monitoring Anticoagulant Therapy Observational Study: Rationale and Protocol - Camporese, Giuseppe; Bernardi, Enrico; Bortoluzzi, Cristiano; Noventa, Franco; Hong, Ngoc Vo; Callegari, Elena; Villalta, Sabina; Tonello, Chiara; Nardin, Michela; Campello, Elena; Spiezia, Luca; Simioni, Paolo (Frontiers in Medicine, 2021)
Real-life studies complement data from registrative trials. Because of the delayed registration of direct oral anticoagulants in Italy, scarce real-life data on such treatments is available for the Italian population. The aim of the MAC project is to collect real-life clinical information in unselected patients given oral anticoagulants for venous thromboembolism, during a 5-year follow-up period.This is a prospective-cohort, multi-center, observational study performed in 4 Italian centers. The estimated samples size is 4000 patients The efficacy outcomes are: incidence of symptomatic recurrent venous thromboembolism and of post-thrombotic syndrome. The safety outcomes are: incidence of major bleeding, clinically relevant non-major bleeding, minor bleeding, serious adverse events, and mortality The MAC project has the potential to improve our understanding of the epidemiology and of the therapeutic strategies adopted in Italian patients with venous thromboembolism Trial Registration: ClinicalTrials.Gov NCT0432939